Gender Concepts and Gender Stereotypes in a Linguistic Picture of the World - Yuliia Petrivna Maslova; Walery Zukow (Journal of Education, Health and Sport, 2017)
The article comprehends the notion of a concept and a stereotypes in the linguistic picture of the world through the prism of a gender perspective. The linguistic and philosophical interpretations of the above concepts by well-known scholars are described, special attention is paid to their scientific research. The observation of the city of the world is based on the understanding of the following: the name of the city of culture, the historical city of culture, the special culture of the world, the city of culture, the information picture of the world. The gender stereotypes, concepts and the conceptosphere in interaction with the language are analyzed in detail.